Facilitators and barriers of relatives' involvement in nursing care decisions and self-care of patients with acquired brain injury or malignant brain tumour: A scoping review protocol. - Rikke Guldager; Mia Ingerslev Loft; Sara Nordentoft; Lena Aadal; Ingrid Poulsen (PLoS ONE)
Introduction Involving relatives can contribute to better quality of care and treatment, and lead to higher satisfaction with hospitalisation in the patients, relatives and healthcare professionals. Nurses play an important role in developing a trusting relationship and facilitating relatives' involvement, since they are around the patient and relatives all day. Thus, involvement is central to the nursing practice. However, involving relatives seems complex and multifaceted with many possible facilitators and barriers to nurses.' Objective The objective of this scoping review is to identify and map the available evidence concerning possible facilitators and barriers to nurses involving relatives in the course of treating disease in individuals who have sustained an acquired brain injury or malignant brain tumour in all settings. Methods and analysis The proposed scoping review will be performed following the Joanna Briggs Institute's (JBI) methodology for scoping reviews. Indexed and grey literature in English, Scandinavian or German languages from 2010 to the present will be considered. The searches will be conducted using bibliographic databases: Medline (via PubMed), CINAHL (via EBSCO) and EMBASE (via OVID). Two reviewers will independently screen the studies and determine if their title, abstract and full text meet the study's inclusion criteria. In case of disagreement, a third and fourth reviewer will be consulted. A customised data extraction form will be used to extract data from the included studies. The results will be presented in tabular form, accompanied by a narrative summary related to the objective of the present scoping review. This scoping review will consider studies that involve nurses caring for individuals with an acquired brain injury or malignant brain tumour in all settings (community, primary care, health care centres, hospital and long-term care institutions). Studies will be included if they describe any kind of facilitators or barriers to involving relatives, and the review will consider all study designs.